History of Sonnet: The Influence of Italian, Spanish, and French Sonneteers on the Elizabethan Sonnet (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The sonnet continued to flower andflourish in Italy during the fifteenth and the sixteenth centuries. By thesixteenth century, it had spread to Spain and France. It reached Englandthrough the work of Wyatt and Surrey in the first half of the sixteenthcentury. After their deaths, it was not practised for some years. Thus Sidneyled the way to a great outburst of sonneteering. Thus sonneteering became apopular habit, a conventional code, a modish artifect of gallanty andcompliment. No poet between 1590 and 1600 failed to try his poetic skill atthis poetic device. During those ten years, more sonnets were composed inEngland than in any other decade. Thus, the Elizabethan sonnet took two forms :(i) the Italian or Petrarchan; (ii) the English or Shakespearean form. Duringthis period, both kinds flourished to the full. But the English form of thesonnet flourished better than the foreign model. Wyatt began with a group of theItalian type. Surrey introduced the English form. The Elizabethan sonnets oweda great deal to the French sonneteers who had preceded them. It wascontemporary French, rather than older Italian influences which first stirredin the Elizabethan mind a fruitful interest in the sonnet. The firstinspiration came from Clement Marot the protestant French poet of the earlyyears of the sixteenth century, who was a contemporary to Wyatt and Surrey. Hestudied Petrarch with ardour, translated into French some of his sonnets andodes and made two or three original experiments in the sonnet form under thetitle of Esigrammar. After his death, Ronard and his companionscontinued writing sonnets. Thomas Watson was the earliest Elizabethan to make areputation as a sonneteer.